SOUTH SUDANESE CULTURAL IDENTITY PORTRAYED BY THE MAIN CHARACTERS IN “THE GOOD LIE” FILM - Ayuliyah, Ayuliyah; Nasta, Mardiyanah (Journal of English Literature and Linguistic Studies, 2025)
This study aims to explore the portrayal of South Sudanese cultural identity in the film The Good Lie, focusing on the main characters' efforts to maintain their cultural heritage while facing the challenges of displacement and resettlement in the United States. Using Evason (2018) theory of South Sudanese cultural identity and Roland Barthes' semiotic analysis, this study examines the ways in which South Sudanese cultural values, traditions, and social ties are portrayed in the film. The analysis highlights key cultural elements such as family ties, religious practices, and food sharing customs, which play an important role in preserving identity amidst change. The findings suggest that The Good Lie not only represents the resilience of Sudanese refugees in maintaining their cultural roots but also sheds light on the structural barriers that influence their resettlement process. This research contributes to discussions on cultural representation in media and provides insight into the complexities of identity preservation among displaced communities.